Construction and characterization of a BAC library for sunflower (Helianthus annuus L.) - Özdemir, NR; Horn, R; Friedt, W (SPRINGER, 2004)
Abacterial artificial chromosome (BAC) library was constructed using the sunflower ( Helianthus annuus L.) restorer line RHA325, which carries the restorer gene Rf1 and the Pl2-gene conferring resistance to downy mildew. High molecular weight DNA was prepared from nuclei using leaf material from two-week old seedlings. The library was constructed using the HindIII site of pBeloBAC11. The current BAC library comprises 104,736 clones. The insert size of the clones varied between 20 and 270 kb, with an average insert size of 60 kb. The whole 1.9 x sunflower BAC library was spotted in duplicate on four high-density filters, each carrying 55,296 clones. The content of organellar DNA, which was estimated by colony hybridisation against the mitochondrial probe coxI and the chloroplast probe rbcL, proved to be less than 0.03 and 0.1%, respectively. BAC pools, allowing PCR-based screening, were made and used to identify positive BAC clones for the markers OP-K13(-)454, closely linked to the restorer gene Rf1. The PCR-based screening was verified by the results obtained for this marker by colony hybridisation.
Keywords: BAC library; helianthus annuus; HMW DNA; PFGE; sunflower; ARTIFICIAL CHROMOSOME LIBRARY; MEGABASE-SIZE DNA; DISEASE-RESISTANCE; ESCHERICHIA-COLI; BACTERIAL; CLONING; GENE; MAP; IDENTIFICATION; CLONES; Agriculture; Plant Sciences